Controlling dispersion and accessibility of Pd nanoparticles via 2D-to-3D zeolite transformation for shape-selective catalysis: Pd@MWW case. (December 2019) - Zhang, Y.; Fulajtárová, K.; Kubů, M.; Mazur, M.; Shamzhy, M.; Hronec, M.; Čejka, J.
Abstract: Metal nanoparticles (NPs) can be encapsulated into zeolites to prepare active catalysts. However, when using conventional encapsulation methods, the location of metal NPs cannot be controlled, which limits the dispersion of metal precursors. Here, we report a new strategy for the encapsulation of Pd NPs into an MWW zeolite during its 2D-to-3D transformation by introducing diethylenediamine palladium (II) acetate, Pd(en)2 (ac)2, when swelling the layered zeolite precursor at room temperature. The resulting Pd@MCM-22 catalyst was investigated by X-ray diffraction, nitrogen sorption, ICP-OES, FTIR, and electron microscopy. The results showed a uniform distribution of NPs in the Pd-doped sample, which had the same nanoporous character as the 'standard' MWW zeolite. Moreover, the Pd@MCM-22 catalyst showed high shape selectivity and activity for the hydrogenation of 3-nitrotoluene and almost no activity for 1-nitronaphthalene. In total, 15 zeolites with different topologies have layered representatives that can be functionalized using this strategy, thereby enabling us to prepare numerous tunable microporous structures, with different zeolite-encapsulated metal NPs specifically designed for shape-selective hydrogenations. Graphical abstract: Image 1 Highlights: 2D-to-3D layered zeolite precursor transformation. Pd nanoparticles of controllable size incorporated into the zeolite pore system. Pd@MWW zeolite shape-selectively catalyzes hydrogenation of nitroarenes. Active and highly selective catalyst for hydrogenation of 3-nitrotoluene.